2014
DOI: 10.1016/j.msec.2014.06.044
|View full text |Cite
|
Sign up to set email alerts
|

Tailored sequential drug release from bilayered calcium sulfate composites

Abstract: The current standard for treating infected bony defects, such as those caused by periodontal disease, requires multiple time-consuming steps and often multiple procedures to fight the infection and recover lost tissue. Releasing an antibiotic followed by an osteogenic agent from a synthetic bone graft substitute could allow for a streamlined treatment, reducing the need for multiple surgeries and thereby shortening recovery time. Tailorable bilayered calcium sulfate (CS) bone graft substitutes were developed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…Still, different inorganic powder properties have been previously modified in an attempt to control the drug release kinetics, though mostly in a robust, unsystematic way, allowing for no truly tunable controlled release to be achieved. These intrinsic parameters have included the powder composition, particle size, crystallinity, porosity, concentration of dopants, polymorphic transitions, particle shell-to-core volume ratio, rotation speed of nanoparticles in a nanomotor, and so on. In this study, we demonstrate for the first time that the kinetics of the mechanism of formation of a solid compound can be controlled to produce tunable and numerically fittable drug release profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Still, different inorganic powder properties have been previously modified in an attempt to control the drug release kinetics, though mostly in a robust, unsystematic way, allowing for no truly tunable controlled release to be achieved. These intrinsic parameters have included the powder composition, particle size, crystallinity, porosity, concentration of dopants, polymorphic transitions, particle shell-to-core volume ratio, rotation speed of nanoparticles in a nanomotor, and so on. In this study, we demonstrate for the first time that the kinetics of the mechanism of formation of a solid compound can be controlled to produce tunable and numerically fittable drug release profiles.…”
Section: Discussionmentioning
confidence: 99%
“…The physical parameters used before with limited success include the particle size, 7 crystallinity, 8 porosity, 9 the dopant concentration 10 and the particle shell-to-core volume ratio. 11 An earlier study demonstrated that the kinetics of the formation of a material can be controlled to produce drug release profiles tunable in situ to anywhere between 1 hour and 2 weeks of total release. 12 Specifically, mixing two differently synthesized hydroxyapatite (HAp) powders with a seemingly identical crystallinity and microstructure in different ratios allowed for the in situ adjustment of the rate of release of different antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…A more intuitive sequential delivery release profile is one with immediate release of the first molecule and a delayed release of the second molecule (Figure 3, Profile 2 [199,200]). This pattern of delivery may be more suitable for applications with antagonistic effects between early and late stage molecules.…”
Section: Sequential Delivery Profilesmentioning
confidence: 99%
“…L-b-L architecture has helped to sequentially deliver growth factors [13,239,248,270,278,279], low Mw drugs [280][281][282] and oligonucleotides [283]. Surprisingly, this physical entrapment was shown highly effective in delaying the release of small molecules (low mw drugs and oligonucleotides).…”
Section: Layer-by-layer (L-b-l)mentioning
confidence: 99%